Evaluating the Impact of Technology Interventions on Organizational Development from an Ethical and Values Perspective - Castillo, Maria Victoria R.; Tiwari, Siddhartha Paul (Archives of Business Research, 2023)
Technology has the potential to be one of the fastest-growing fields in the world in the near future, and it has the ability to revolutionize a number of areas including overall society, education, and banking as a result in the near future. In spite of the fact that technology has been omnipresent in our day-to-day lives for quite some time now, the advent of language models and smart home devices has created a need for an ethical discussion on the associated risks as well as responsibilities associated with language models and smart home devices. Whenever a set of technologies is developed and deployed, it is crucial to ensure that a set of ethical values are followed as a guide; this is because the use of these technologies can have a significant impact on people's lives.